Research on the Effectiveness of Microsoft’s Acquisition of Activision Blizzard - Fu Yiqiao (SHS Web of Conferences)
In January 2022, Microsoft announced the acquisition of Activision Blizzard Inc. This article mainly explores the performance changes of this merger and acquisition, as well as the impact and inspiration of the merger on the enterprise. Firstly, this article introduces the basic information of both parties involved in the merger and acquisition, as well as their situation in the gaming industry. Secondly, the merger process is introduced through the selection of merger targets and changes in merger performance. Finally, this article summarizes the potential impact of this merger on the gaming industry and the insights it brings to other companies. The results indicate that this acquisition not only strengthens Microsoft’s competitiveness in the gaming industry, but also brings new opportunities for Activision Blizzard, which has important reference value. Furthermore, companies expanding globally must adapt IP content to local cultural and market contexts to optimize user satisfaction and drive international growth.